Zatrzymana, kluczowa wiedza niejawna (ZKWN) jako instrument koordynacji w przedsiębiorstwach sieciowych - Perechuda, Kazimierz (Knowledge Coordination in the Net Enterprises, 2005)
In the paper are presented: main issues of the knowledge coordination, the types of the net coordination, coordination requirements, crucial role of the knowledge coordination, lifecycle of the net coordination.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1064, s. 209-216